1993
DOI: 10.1200/jco.1993.11.11.2234
|View full text |Cite
|
Sign up to set email alerts
|

Improved therapy for children with acute lymphoblastic leukemia and unfavorable presenting features: a follow-up report of the Childrens Cancer Group Study CCG-106.

Abstract: Both Reg A and Reg B provided a better outcome than Reg C for children with acute lymphoblastic leukemia and unfavorable presenting features. Outcomes on Reg A and Reg B were similar. Use of the more effective but more toxic regimens resulted in 78 additional hospital days per relapse prevented on Reg A and 101 days on Reg B. The current CCG trial for this population builds on Reg A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 29 publications
1
58
0
2
Order By: Relevance
“…Progress achieved with specific treatment strategies for the different risk groups in the 1983-1988 era is shown in Table 2. The reported advantage for the CCG-modified BFM regimen for higher risk patients, either without (CCG-106) 23 or with (CCG-123) 21 lymphomatous features is maintained with longer follow-up (Figure 3a and b). On CCG-106, the 10-year EFS estimates for CCG-modified BFM therapy vs standard therapy are 63% and 42%, respectively (Table 2).…”
Section: Figurementioning
confidence: 83%
See 2 more Smart Citations
“…Progress achieved with specific treatment strategies for the different risk groups in the 1983-1988 era is shown in Table 2. The reported advantage for the CCG-modified BFM regimen for higher risk patients, either without (CCG-106) 23 or with (CCG-123) 21 lymphomatous features is maintained with longer follow-up (Figure 3a and b). On CCG-106, the 10-year EFS estimates for CCG-modified BFM therapy vs standard therapy are 63% and 42%, respectively (Table 2).…”
Section: Figurementioning
confidence: 83%
“…10,[14][15][16]21,23,25,26,30,51,52 The day 7 and day 14 marrow response to therapy has been a consistent prognostic factor. [53][54][55] Improved systemic therapy has allowed restriction of brain irradiation to fewer than 15% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Potential reasons for these neurotoxicities have been reviewed in a previous publication, 34 Overall outcome data from this clinical trial compare favorably with previous POG trials and those of other groups treating children for HR-ALL (62-75%). [9][10][11][12][13][14][15][16][17][18][19][20] Because risk group criteria differ among large cooperative groups treating childhood ALL, external comparisons are difficult and hazardous. However, 66% of the patients in this study would be considered high risk by the CTEP/NCI consensus risk group definition (age у10 years, or WBC у50 000) thus adding some validity to cross comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, improvement in survival was realized for patients with HR-ALL. [9][10][11][12][13][14][15][16][17][18][19][20] Increased toxicity was also noted with the aggressive use of myelosuppressive agents. 9,13,14,16,18,[19][20][21][22] However, preliminary results from POG 8698 suggested that early intensification with the less toxic combination of intermediate-dose methotrexate (MTX) and mercaptopurine (MP) might be as effective as the more myelosuppressive combinations used in another POG pilot study (POG 8398) for HR-ALL.…”
Section: Introductionmentioning
confidence: 99%